Consumer culture theory - Cross, Samantha N. N.; Ruvalcaba, Cecilia; Venkatesh, Alladi; Belk, Russell W. (Research in consumer behavior ;, 2018)
This series epitomizes the 2017 Consumer Culture Theory (CCT) conference themes of hyper-reality and cultural hybridization. The partnership of the co-editors, with diverse backgrounds including Caribbean, Mexican and Indian roots, itself depicts cultural hybridity, culminating in a series of fascinating articles written by authors from around the globe. The eleven research papers provide a global perspective on a range of consumer discourses both in the physical marketplace (research on mobility practices within the transportation market in Vietnam; or an examination of stigma in beef consumption practices in India), or in the virtual marketplace (a study of the discourses surrounding the mythic nature of Bitcoin creator, Satoshi Nakamoto; or parental management understood through the media marketplace experiences of black women in Britain). The conference's Best Competitive Award paper is featured; a compelling look at hyper-reality within the world of the Broadway musical, examining how new media platforms are used to appeal to new and existing consumers. This series also includes two insightful papers on wine producers and their cultural intermediaries, and on wine tourism, where the authors traverse the globe to better understand market development and consumer engagement respectively. Whether it be an examination of consumer tribes, breast cancer and gender identity, or product gender and design, these authors collectively provide us with unique and riveting perspectives on consumer and marketplace experiences. The series fittingly culminates with a critical look at the emergence of the CCT tradition; an emergence that is both timely and important as this series demonstrates.